PENGARUH THE BIG-FIVE PERSONALITY TRAITS TERHADAP INVESTMENT INTENTIONS DENGAN ATTITUDE TOWARDS FINANCIAL RISK SEBAGAI VARIABEL MEDIASI - Muhammad Kevin Kautsar Herman; Ossi Ferli (Ibs Press, 2023)
Investment intentions in Indonesia still have a low percentage, only 3% teens in Indonesia who can see the opportunity in investment. The purpose of this research is to find the effect of The-Big Five Personality Traits, Attitude towards Financial Risk, Short-Term Investment and Long-Term Investment. This study uses a questionnaire as a measuring tool, which consists of several questions and distributed to the Jabodetabek with some criteria including Z and Y respondent, 151 respondents fill up the questionnaire. This research uses Path Analysis method with AMOS-SPSS programs. The results are two variables from The Big-Five Personality Traits had effects on Attitude towards Financial Risk. Other than that, The Big-Five Personality Traits had indirect effect to Short-Term and Long-Term Investment.